2020
DOI: 10.1111/and.13755
|View full text |Cite
|
Sign up to set email alerts
|

Does Lepidium meyenii (Maca) improve seminal quality?

Abstract: Andean Maca (Lepidium meyenii) is a herbaceous biennial or annual plant native of the high central Andes of Peru that grows exclusively at altitudes ranging from 4,000 to 4,500 m above sea level. Three different types of maca can be found depending on the colour of its dry root (red, yellow or black), each of which has been attributed several medicinal properties (Gonzales, Villaorduña, Gasco, Rubio, & Gonzales, 2014). The composition of maca comprises nearly 55%-60% carbohydrates, 10%-12% proteins, 8%-9% fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In our search, 352 articles were identified, and five of these met the criteria for inclusion ( Kim, 2011 ; Poveda et al, 2013 ; Melnikovova et al, 2015 ; Alcalde and Rabasa, 2020 ; Melnikovova et al, 2021 ) ( Figure 1 ; Table 1 ). Among these, one RCT each was conducted in Spain ( Alcalde and Rabasa, 2020 ), Korea ( Kim, 2011 ), and Panama ( Poveda et al, 2013 ), and two RCTs were conducted in the Czech Republic ( Melnikovova et al, 2015 ; Melnikovova et al, 2021 ). Across all five studies, maca (1–5 g) was administered orally to the participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our search, 352 articles were identified, and five of these met the criteria for inclusion ( Kim, 2011 ; Poveda et al, 2013 ; Melnikovova et al, 2015 ; Alcalde and Rabasa, 2020 ; Melnikovova et al, 2021 ) ( Figure 1 ; Table 1 ). Among these, one RCT each was conducted in Spain ( Alcalde and Rabasa, 2020 ), Korea ( Kim, 2011 ), and Panama ( Poveda et al, 2013 ), and two RCTs were conducted in the Czech Republic ( Melnikovova et al, 2015 ; Melnikovova et al, 2021 ). Across all five studies, maca (1–5 g) was administered orally to the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs reported random sequence generation methods and employed allocation concealment ( Melnikovova et al, 2015 ; Alcalde and Rabasa, 2020 ; Melnikovova et al, 2021 ) ( Figure 2 ). The double-blind design was used in all five studies, but the baseline between the three groups was significantly different ( Melnikovova et al, 2015 ; Alcalde and Rabasa, 2020 ; Melnikovova et al, 2021 ). Notably, one RCT was published in the form of an abstract, and most of the domains were unclear ( Poveda et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our double‐blind placebo‐controlled trial, we have observed some irrelevance in the data obtained compared with our review of the literature. According to Alcalde and Rabasa ( 2020 ), sperm concentration increased in infertile adult men treated with maca compared with placebo. Our results reported as the total sperm count increased by 15% in patients using maca for the period of 16 weeks, but we noticed doubling of total sperm count in the placebo group.…”
Section: Discussionmentioning
confidence: 99%